Depositional Environment of Fine-Grained Sedimentary Rocks of the Sinamar Formation, Muara Bungo, Jambi - Zajuli, M. Heri Hermiyanto; Panggabean, H. (Indonesian Journal on Geoscience, 2013)
DOI:Â 10.17014/ijog.v8i1.153The research area is situated in the northwestern side of South Sumatra Basin, which is a part of Muara Bungo Regency, Jambi Province. The Oligocene Sinamar Formation consists of shale, claystone, mudstone, sandstone, conglomeratic sandstone, and coal-seam intercalations. This research was focused on fine sedimentary rock of Sinamar Formation, such as shale, claystone, and mudstone. Primary data were collected from SNM boreholes which have depths varying from 75 m up to 200 m, and outcrops that were analyzed by organic petrographic method, gas chromatography-mass spectrometry (GC-MS) of normal alkanes including isoprenoids, and sterane. The dominant maceral group is exinite, composed of alginite (3.4 - 18%), and resinite (1.6 - 5.6%), while vitrinite maceral consists of tellocolinite 0.4 - 0.6%, desmocollinite 0.4%, and vitrodetrinite 8.4 - 16.6%. Organic petrography and biomarker analyses show that organic materials of shales were derived from high plants and algae especially Botrycoccus species. Botrycoccus and fresh water fish fossil, found in the shale indicate a lacustrine environment.